Investigation of PMD in direct-detection optical OFDM with zero padding - Li, Xiang (2013)
We investigate the polarization-mode dispersion (PMD) effect of zero padding OFDM (ZP-OFDM) in direct-detection optical orthogonal frequency division multiplexing (DDO-OFDM) systems. We first study the conventional equalization method for ZP-OFDM. Then an equalization method based on sorted QR decomposition is proposed to further improve the performance. It is found that the performance improvement of ZP-OFDM is due to the frequency domain oversampling (FDO) induced inter-carrier interference (ICI). Numerical simulation results show that compared with cyclic prefix OFDM (CP-OFDM), ZP-OFDM has a significantly higher tolerance to PMD in DDO-OFDM systems when the channel spectral nulls occur at certain differential group delay (DGD) values.